The ADRENAL score: A comprehensive scoring system for standardized evaluation of adrenal tumor - Zhou, Xiaochen; Li, Xuwen; Fu, Bin; Liu, Weipeng; Zhang, Cheng; Xia, Yu; Gong, Honghan; Zhu, Lingyan; Lei, Enjun; Kaplan, Joshua; Deng, Yaoliang; Eun, Daniel; et al. (Frontiers in Endocrinology, 2022)
Objectives: To propose an original and standardized scoring system to quantify the functional and anatomical characteristics of adrenal tumor. Materials and Methods: Four groups of consecutive adrenalectomies (n = 458) with heterogeneity in tumor characteristics and surgical approaches, including 212 laparoscopic cases (Group 1) and 105 robotic cases (Group 2) from The First Affiliated Hospital of Nanchang University, 28 robotic cases from Temple University Hospital (Group 3) and 113 laparoscopic cases from The First Affiliated Hospital of Guangxi Medical University (Group 4). All patients were followed up for 4.5 to 5.5 years. Six parameters including functional status or suspicion of malignancy, tumor size, relationship to adjacent organs, intratumoral enhancement on CT, nearness of the tumor to major vessels and body mass index were assessed and scored on a 0, 1 and 2 points scale. Correlation between the sum of the 6 scores and tumor laterality (ADRENAL score) verse operative time (OT), estimated blood loss (EBL), perioperative complications, transfusion, conversion and length of hospital stay was analyzed. Results: ADRENAL score was a strong predictor of both OT and EBL in all four groups (p < 0.05 for all tests). In Group 2 and 4, higher ADRENAL score seemed to correlate with longer hospital stay. No statistically significant correlation between ADRENAL score and complication, transfusion or conversion was noted yet. Conclusions: ADRENAL score appears to be a valid predictor of surgical outcomes. It may provide a common reference for adrenal surgery training program, preoperative risk assessment and stratified comparative analysis of adrenal surgeries via different techniques and approaches.